2001
DOI: 10.1002/ijc.1028
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term sexual function after prostate brachytherapy

Abstract: SUMMARY Sexual function was evaluated in 34 patients with low-risk prostate cancer (PSA ≤ 10, Gleason score ≤ 6, clinical stage T1/T2) undergoing brachytherapy in a phase III prospective randomized trial comparing iodine-125 ( 125 I) to palladium-103 ( 103 Pd). The mean and median International Index of Erectile Function (IIEF) scores for the entire group were 14.2 and 16.5, respectively, and there was no difference between these scores when stratified by isotope. IIEF scores < 6, 6 to 11, and ≥ 12 were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
9

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 15 publications
2
27
0
9
Order By: Relevance
“…Although ejaculatory pain in the general male population is considered to be 1%, 1 it is presented a serious problem for 88-91% of men who experience it. 2,3 It can be caused by prostatectomy, 4,5 a history of prostatitis, 6 pelvic radiation, 7,8 lower urinary tract symptoms (LUTS) diagnosed with clinical benign prostatic hyperplasia (BPH), 9,10 chronic pelvic pain disorder, 11 and neuroleptics. [12][13][14][15][16][17][18] On the other hand, PE as a sole entity is rare, and its etiology often remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although ejaculatory pain in the general male population is considered to be 1%, 1 it is presented a serious problem for 88-91% of men who experience it. 2,3 It can be caused by prostatectomy, 4,5 a history of prostatitis, 6 pelvic radiation, 7,8 lower urinary tract symptoms (LUTS) diagnosed with clinical benign prostatic hyperplasia (BPH), 9,10 chronic pelvic pain disorder, 11 and neuroleptics. [12][13][14][15][16][17][18] On the other hand, PE as a sole entity is rare, and its etiology often remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall incidence of ED following external-beam radiation ranges from 41%-85% (Table 1) [5][6][7][8][9][10][11][12][13][14][15] and is dose-and age-dependent. 4 Three-dimensional conformal therapy (3D-CRT) may enhance the chance of preservation of erectile function sufficient for vaginal penetration the majority of patients.…”
Section: External-beam Radiation Therapymentioning
confidence: 99%
“…Reports from the literature show that 6-53% of patients could develop ED after permanent seed implantation. [1][2][3][4][5][6][7][8] These reported wide ranges of ED probably reflect differences in the length of followup, patient selection and the mode of data collection. In general, the series with longer follow-up periods show lower rates of potency preservation.…”
Section: Introductionmentioning
confidence: 99%
“…10 Several factors, including preimplant potency, patient age, the use of supplemental external-beam irradiation, radiation dose to the prostate gland, radiation dose to the bulb of the penis and diabetes mellitus, appear to exacerbate brachytherapy-related ED. 8,[12][13][14][15] DiBiase et al 16 have proposed that postimplant ED could be caused by the radiation damage to the nerve bundles and vascular structures. Some studies reported a strong correlation between the dose of radiotherapy delivered to the bulb of the penis and ED, 14,15 while others found no such correlation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation